Características estruturais da madeira de pinus elliottii Engelm aos 30 anos de idade - Clovis Roberto Haselein (Ciência Florestal, 2000)
In this study, six trees from a 30 year slash pine stand were harvested. The stumps were converted into 2,5 m logs and the two first were processed into pith centered cants. After airseasoning, the cants were transformed into small clear static bending specimens according to ASTM D143-93 (1995). Samples were taken near the pith and the bark. Bending stiffness (MOE) and strength (MOR) and basic density measured at 12% moisture content were related to the number of growth rings and percentage summer wood determined at every specimen cross-section. Significant differences were found between radial positions. In general, larger increase in properties of the juvenal wood as a function of the increase of the growth rings and percent summer wood were observed.